Consumer adoption of green products and its impact on achieving perceived value A study on a sample of owners of environmentally friendly cars - Thamr Al-Bkry (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The research aims to know the effect of the green consumer to adopt green product and realize the perceived value as a result of this behavior. Application of research on a sample of environmentally friendly vehicles owners in the capital, Amman was carried out. And the search of all persons in the maintenance and parking stations and washing cars community centers in the city of Amman. Where have been accredited as an area for field application of the research was to obtain the required data through personal interviews and using the questionnaire as a tool for data collection, and the sample was a simple random sample of individuals environmentally friendly vehicles owners (Hybrid) amounted to (240) per person. After conducting the analysis process research concluded Head is the presence of a statistically significant effect at the level of significance (a ³ 0.05) in the consumer adoption of green product to achieve the perceived value of the behavior. Research has recommended a number of recommendations, notably the work to strengthen the position of mind among consumers in this type of green products and lend real confidence to interact with them, and on the top departments in the green trends organizations, specifically in the field of cars to reconsider the social and ethical responsibility towards society and the environment, by giving the environmental dimension greater importance in their own marketing strategies.